Similarities and differences in the response and molecular characteristics of peripheral sensory neurons associated with pain and itch - Liu Li; Yin Jiemin; Meng Youqiang; Ye Congrui; Chen Junhui; Wang Sa; Yin Wen; Gao Po; Jiao Yingfu; Yu Weifeng; Fan Yinghui (Acta Biochimica et Biophysica Sinica)
Dorsal root ganglion (DRG) neurons are responsible for the primary detection and transmission of peripheral noxious stimuli, mainly pain and itch. However, as two distinct noxious sensations, how DRG neurons respond differently to and code pain and itch is still an attractive topic. Here, we investigate the response and activation spectrum of DRG neurons under peripheral pain and itch stimuli using in vivo two-photon calcium imaging and find differences in the response intensity to pain and itch between multisensory neurons (both pain and itch) and single-sensory neurons (either pain or itch). In addition, single-cell RNA sequencing (scRNA-seq) is used to reveal the heterogeneity of distinct subpopulations on the basis of their expressions of pain- or itch-related marker genes and to determine the similarities and differences in their transcriptomic changes under chronic pain and itch. Our results show that primary sensory neurons with different sensory patterns respond differently to the same nociceptive stimuli. Additionally, distinct clusters of neurons exhibit unique transcriptomic changes in the development of chronic pain and itch, which may offer new insights for treating these conditions.